2004
DOI: 10.1016/j.amjhyper.2004.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Initial angiotensin-converting enzyme inhibitor/calcium channel blocker combination therapy achieves superior blood pressure control compared with calcium channel blocker monotherapy in patients with stage 2 hypertension*1

Abstract: Combination therapy was well tolerated and resulted in significantly greater BP reductions and attainment of BP goals compared with monotherapy in patients with stage 2 hypertension. This evidence supports the recommendation of combination therapy as first-line treatment in stage 2 hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 20 publications
3
36
2
1
Order By: Relevance
“…We identified a substantial effect of A therapy (B25/11 mm Hg) and an additional BP lowering (B5/3 mm Hg) attributable to the combination of amlodipine and benazapril. The observation that BP control rates in this study are lower than those reported in other studies, 6,7 owes, at least in part, to the very high baseline SBP and DBP measurements that were present (about 175/100 mm Hg); thus, a mean decrease in SBP of 435 mm Hg and DBP of 420 mm Hg would have been necessary to achieve BP control in the majority of subjects. More important is the strict guideline-based definition of BP control that was used (o140/90 in general or o130/80 mm Hg in subjects with diabetes or CKD).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…We identified a substantial effect of A therapy (B25/11 mm Hg) and an additional BP lowering (B5/3 mm Hg) attributable to the combination of amlodipine and benazapril. The observation that BP control rates in this study are lower than those reported in other studies, 6,7 owes, at least in part, to the very high baseline SBP and DBP measurements that were present (about 175/100 mm Hg); thus, a mean decrease in SBP of 435 mm Hg and DBP of 420 mm Hg would have been necessary to achieve BP control in the majority of subjects. More important is the strict guideline-based definition of BP control that was used (o140/90 in general or o130/80 mm Hg in subjects with diabetes or CKD).…”
Section: Discussioncontrasting
confidence: 71%
“…More important is the strict guideline-based definition of BP control that was used (o140/90 in general or o130/80 mm Hg in subjects with diabetes or CKD). We have found only two studies with limited similarity: SOLACE by Jamerson et al 6 and SHIELD by Bakris et al, 7 in which BP control rates were 61 and 63%, respectively. Each of these studies was of 12 weeks in duration, whereas our study was much shorter (6 weeks).…”
Section: Discussionmentioning
confidence: 92%
“…First, as CCBs and RAS inhibitors effect vasodilation by different mechanisms, their antihypertensive effects are additive when used in combination. [5][6][7][8]64,65 This effect is exemplified by data from a recent trial involving amlodipine and olmesartan medoxomil, which showed that both the absolute BP reductions achieved and the rate of target BP attainment were significantly greater in patients who received combination therapy than in those who received amlodipine monotherapy. 5 It is important to note that, in contrast to many other studies, the target BP in this trial was defined using both diastolic blood pressure and systolic blood pressure (o140/90 mm Hg for the majority of patients; o130/80 mm Hg for those with diabetes).…”
Section: Other Advantages Of Ccb/ras Inhibitor Combination Therapymentioning
confidence: 85%
“…Combining classes of agents with complementary mechanisms of action, such as CCBs and RAS blockers, provides greater BP-lowering efficacy than monotherapy, [68][69][70][71][72][73][74][75] with a comparable and potentially improved adverse-event profile. 76 However, few trials have been designed to test the effect of specific antihypertensive combinations on cardiovascular or renal end points.…”
Section: Dual Calcium Channel/ras Blockadementioning
confidence: 99%